Developmental and economic consequences of expected population changes in the Russian Federation - Zuzanna Brunarska (University of Warsaw, Centre of Migration Research (CMR), 2017)
The paper discusses economic and developmental consequences of future population changes in Russia, taking into account demographic changes both on the country level and broken down by ethnic group. It focuses on their impact on the labour market, pension system and economy, including regional development, also taking into consideration differences between ethnic groups as regards their demographic and socio-economic characteristics. The role of international migration is discussed separately.
Keywords: 330; Russia; population changes; ethnic groups; migration